Movement Disorders and Musculoskeletal System: A Reciprocal Relationship - Pandey S. (2023)
The association of movement disorders (MDs) with musculoskeletal (MSK) disorders is observed in two principal scenarios. First, MDs patients may present with MSK issues. This phenomenon is primarily observed in parkinsonian syndromes, but may also be seen in patients with dystonia, Tourette syndrome, and some gene-related MDs. Second, there are MSK disorders that may produce or mimic MDs. Important primary MSK disorders producing MDs are joint hyperlaxity syndrome, non-traumatic craniovertebral junction anomalies, congenital muscular torticollis, and rheumatoid arthritis. Peripheral trauma to the MSK system may also lead to MDs commonly referred to as peripherally induced MDs. The exact pathogenesis of these disorders is not clear, however many patients have associated sensory phenomena such as complex regional pain syndrome. Herein, we provide an overview of disorders that may manifest with a combination of MSK and MDs, as detailed above. The most common MDs are discussed in each section, along with important clinical points, suggested diagnostic workups, and possible differential diagnoses.